Glossary Book For Cadets Of Indonesian Railway Academy In English Specific Purpose Program - Widiyanah, Ima; ., Handoko; Damayanti, Ajeng Tyas (Politeknik Perkeretaapian Indonesia Madiun, 2017)
English specific purpose (ESP) is a learner-centered approach to teaching English as additional language, which focuses on developing communicative competence in specific discipline such as academics,  accounting,  agrology,  business,  IT,  teaching,  and  engineering.  ESP  also  defined   to meet specific needs of learners. Accordingly, it is important for the  cadets  to  master  English  for railway in order to prepare them for English technical terminology in working area. This study aimed to identify the problem faced by the cadets of Indonesian Railway Academy and to develop glossary terms based on the cadets? need. In this study, the writer used research and development (R&D) design. It means that the study designed to develop materials for use in ESP program. The population of this study is the cadets of Indonesian Railway Academy.  The  number  of the  subject  was 35 cadets from electrical class. The writer used questionnaire and interview  to  gather  the  data. The result of the study showed that twenty cadets said that  ESP  is  difficult  to  learn,  they also said that there was different English for general  and  English  for  Specific  Purpose.  Fifteen  students  said that they enjoyed ESP program and they also  said  that English  is  important  to learn  to  get  a  job. The writer concludes that the cadets of Indonesian Railway Academy Madiun have to  develop their knowledge about glossary terms for railway to increase their vocabulary.